Cyber Library Auditorium Acoustic Evaluation in Acoustic Phonetic Perspective - Siregar, Iskandarsyah (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
Acoustics is an interdisciplinary science concerned with studying all mechanical waves in gases, liquids, and solids, including vibration, ultrasound, sound, and infrasound. The study of acoustic function is growing to be important today. In the conditions of the development of an all-artificial civilization, it turns out that complementary electronic ornaments are still very dependent on the level of success with the form of the structure and composition of the room itself. The problem arises when an adjustment on one side, intended for improvement, actually shifts the ideal coordinates on the other side. For this reason, a comprehensive adjustment and correction idea should emerge as a solution, with acoustic studies as a starting point. This study tries to describe the ideal design based on investigations and observations of the actual condition of the National University cyber library auditorium and tries to determine the suitable material for the room. The stages carried out in the research can be adapted to the needs of the study. This step is to get the most comprehensive results with the most effective and efficient measures. Integrated software and trial and error analysis are also part of the research method. It was found that the new design of the National University’s cyber library auditorium has good acoustic insulation with some adjustments that are still possible to get the ideal standardization of the room.